Theoretical Limits and Interpolation based Improvements of a Correlation Based True-Speed-Over-Ground Estimation - Reißland, Torsten; Weigel, Robert; Kölpin, Alexander; Lurz, Fabian (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2023)
For a radar based True-Speed-Over-Ground measurement system an interpolation based precision improvement is presented. The system is based on the cross-correlation of two radar receive signals. The theoretical basics of the interpolation are thoroughly introduced and its limits are determined for the general case and for a specific hardware. Measurement results including the interpolation are presented and compared to the former implementation.<br
CRIS-Team Scopus Importer:2023-03-17
Keywords: radar; correlation; interpolation; velocity measurement; rail transportation